EMERGING MEAT PROCESSING TECHNOLOGIES AND THEIR IMPACT ON THE SAFETY AND QUALITY OF MEAT PRODUCTS (Journal of Medical & Health Sciences Review, 2025)
Meat processing technologies play a critical role in ensuring the safety, quality and shelf-life of meat products. Traditional processing methods, including chilling, freezing, curing, smoking and thermal treatments have long been employed to reduce microbial contamination and extend storage life. However, these methods can adversely affect the sensory attributes and nutritional quality of meat. Emerging technologies such as high pressure processing (HPP), pulsed electric fields (PEF), ultrasonication, irradiation, cold plasma and ohmic heating, offer innovative approaches that can enhance microbial safety while better preserving meat quality. This review provides a comprehensive comparison of traditional and modern meat processing techniques, evaluating their effects on microbial inactivation, shelf-life extension, sensory characteristics and nutritional retention. Additionally, the review discusses the regulatory frameworks, industrial adoption challenges and future research trends associated with these technologies. By highlighting the strengths and limitations of both traditional and emerging approaches, this review aims to inform researchers, industry professionals and policymakers about optimal strategies for producing safe and high quality meat products.